Peningkatan keterampilan pemulasaraan jenazah bagi warga Desa Botto Mallangga, Maiwa, Enrekang, Sulawesi Selatan - Agussalim; Abbas Ramadhan; Rosmala; Suherman; Vian Adnan; Muhammad Usriabih Aris; Hasan; Putri Amalia; Fuji Ardiwinata; Megawati; Mahfira; Aliafitri (P3HKI - Universitas Muhammadiyah Parepare, 2022)
There are still people who do not understand the importance of funerals, especially the families of the deceased, making people dependent on funeral services. For example, the law regarding the disposal of corpses is a complement that must be in accordance with Islamic law. It is appropriate for the closest family to handle the body to avoid heresy. Therefore, empowerment is needed to improve corpse-handling skills so that many people can handle corpses. Partners in this activity include residents of Botto Malangga Village and KUA officers of Maiwa District, Enrekang Regency, South Sulawesi. The activities carried out included lecture methods and direct practice from an expert, namely the chairman of the Maiwa District KUA—an activity whose center was at the Nurul Baitul Aqsa Mosque, Botto Mallangga Village. The practice of exorcising a corpse includes delivering a lecture, as well as training in expelling a corpse which begins with washing the corpse, shrouding the corpse, and praying for the corpse. The results of this activity will be obtained if any of the participants have been involved in corpse rotation. After the activity shows that the participant has been able to arrange the corpse according to the stages of the material received, the participant has the skills to dispose of the corpse.